Comparison of Economic Effects of Carbon Taxes and Energy Taxes on Iran's Economy: A Computable General Equilibrium approach - Esfandiar Jahangard; Ali Asghar Banoe; Sajjad Barkhordari; Hamid Amadeh; amir doudabi nezhad (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2019)
Environmental taxes, including carbon and energy price taxes, are one of the most crucial means of market-based approach of reducing Greenhouse Gas Emissions and are widely used around the world In the present research, the effects of enforcing these two tax policies are assessed in two scenarios of redistribution and non-redistribution of the overall tax incomes between households (in sum, four scenarios), based on the CGE model. These two taxes make different impacts on relative prices of energy carriers. Accordingly, they have different economic effects which remained unexamined in previous researches. The results of present study, therefore, would make a clearer anticipation of the future policies effects, which will be implemented to meet the international environmental commitments of Iran. The results of simulations indicate that both taxes lead to emission reduction but carbon taxes are more efficient than energy taxes, because the former requires less amount of taxes, whereas the level of emission reduction is the same. If there’s no redistribution of tax incomes, both kind of taxes decrease the welfare and real consumption budget of households, but in case of redistribution, these indexes will increase. In all scenarios, GDP, decrease and consumer price increase will increase in different amounts and employment in 3 scenarios increase. Based on the findings of present research, enforcing the carbon tax policy, concomitant to tax incomes redistribution, are among the appropriate policies designed to reduce the greenhouse gas emission and meet the international commitments of Iran.